2021
DOI: 10.1128/spectrum.01152-21
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Interactions Drive Distinct Taxonomic and Potential Metabolic Responses to Habitats in Karst Cave Ecosystem

Abstract: In general, the constant physicochemical conditions and limited nutrient sources over long periods in the subsurface support a stable ecosystem in karst cave. Previous studies on cave microbial ecology were mostly focused on community composition, diversity, and the relationship with local environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 64 publications
(87 reference statements)
3
28
0
1
Order By: Relevance
“…Highly diverse bacterial communities were detected from the weathered rocks in caves with the dominance of Proteobacteria , Actinomycetes , and Firmicutes ( Yun et al, 2016 ; Zhu et al, 2019 , 2021 ; Ma et al, 2021 ). In contrast, the diversity of fungi is relatively low due to the limited input of organic matter by photosynthesis in caves ( Lee et al, 2012 ; Man et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Highly diverse bacterial communities were detected from the weathered rocks in caves with the dominance of Proteobacteria , Actinomycetes , and Firmicutes ( Yun et al, 2016 ; Zhu et al, 2019 , 2021 ; Ma et al, 2021 ). In contrast, the diversity of fungi is relatively low due to the limited input of organic matter by photosynthesis in caves ( Lee et al, 2012 ; Man et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 and Table A4, Appendix A -Supplementary data). Both phyla are cosmopolitan and appeared frequently in oligotrophic sediments, but there exists relatively little information about their ecological role (Eichorst et al, 2018;Ma et al, 2021). Collectively, our findings suggest that moonmilk deposit formation in Pindal Cave is closely related to Crossiella and wb1-P19.…”
Section: Bacterial Communities On Cave Formations: From Sediments To ...mentioning
confidence: 75%
“…To the best of our knowledge, there is no study associating Crossiella relative abundance with moonmilk formation, except in the study on a volcanic cave where Crossiella relative abundance was 2.5% (Gonzalez-Pimentel et al, 2021). However, a few authors reported the finding of Crossiella not only in carbonate environments such as weathered rock caves (Ma et al, 2021), but also in deteriorated stone monuments (Li et al, 2018).…”
Section: Bacterial Communities On Cave Formations: From Sediments To ...mentioning
confidence: 99%
“…In an acidic cave system, dominant species of bacteria displayed high variability in different microhabitats as a function of pH (Yun et al., 2016). However, how microorganisms inhabit a hyperalkaline environment remains underexplored, especially in a dark and oligotrophic cave setting (Dong et al., 2020; Ma et al., 2021).…”
Section: Introductionmentioning
confidence: 99%